2023
DOI: 10.1002/ana.26617
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rest–Activity Rhythms, Delirium Risk, and Progression to Dementia

Abstract: Objective Delirium is a complex neurocognitive syndrome suspected to be bidirectionally linked to dementia. Circadian rhythm disturbances likely contribute to dementia pathogenesis, but whether these disturbances are related to delirium risk and progression to all‐cause dementia is unknown. Methods We analyzed continuous actigraphy data from 53,417 middle‐aged or older UK Biobank participants during a median 5 years of follow‐up. Four measures were used to characterize the 24‐hour daily rest–activity rhythms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Fluctuations of symptoms and intensity of delirium suggest an altered circadian rhythm. 41 Recent evidence also indicates that circadian disturbances predispose to delirium, 25 suggesting a bidirectional relationship. In this study, we accounted for sleep duration, and the association between depression symptom burden and delirium remained after controlling for known dementia and excluding preexisting dementia (or "delirium superimposed on dementia" cases).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluctuations of symptoms and intensity of delirium suggest an altered circadian rhythm. 41 Recent evidence also indicates that circadian disturbances predispose to delirium, 25 suggesting a bidirectional relationship. In this study, we accounted for sleep duration, and the association between depression symptom burden and delirium remained after controlling for known dementia and excluding preexisting dementia (or "delirium superimposed on dementia" cases).…”
Section: Discussionmentioning
confidence: 99%
“…CVD was based on hypertension, high cholesterol, smoking, diabetes, ischemic heart disease, and peripheral vascular disease. Comorbidities included a previously described morbidity burden 21,25,26 based on the summed presence of any cancers, respiratory, neurological, gastrointestinal, renal, hematological, endocrine, musculoskeletal, connective tissue, infectious diseases/disorders, and classified as none (0)/modest (1-3)/high (≥4) conditions. Cognitive performance was estimated at initial enrollment using a raw processing speed test involving the mean reaction time to identify card matches correctly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such symptoms of these issues include insufficient sleep, irregular timing, unscheduled naps, insomnia or daytime sleepiness 13. Sleep/circadian disruption increases with age and cognitive impairment and is associated with frailty,14 pain and opioid use,15 preclinical AD pathology16 17 and the onset of AD/ADRD 18. POD is associated with disruption of melatonin secretion—the key circadian hormone in sleep homoeostasis,19 particularly, in older patients 20.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work and those by others have shown that suboptimal sleep/circadian regulation predicts POD risk [812] and progression to dementia, independent of age, sex, education, and cognition. [13] These studies also uncovered that sleep/circadian measures correlated with CSF amyloid/tau burden decades before dementia,[14,15] and that plasma tau burden was associated with PND in two surgical cohorts. [16,17] Finally, the APOE -ε4 genotype interacts with sleep to affect AD risk,[18] but its role in POD remains controversial.…”
Section: Introductionmentioning
confidence: 99%